Feminist masculinities: a transformative approach - Moura, Tatiana (Frontiers in Political Science, 2025)
This article proposes the notion of feminist masculinities as a transformative solution to the global re-emergence of antifeminist politics, especially those based on right-wing populism and regressive gender ideologies. While previous research has primarily focused on the ideological content and mobilization strategies of antifeminism, less attention has been given to men who actively oppose such narratives and engage in feminist-aligned practices. Drawing on the scholarship of bell hooks, Connell and Messerschmidt, and feminist care ethicists, the article theorizes feminist masculinities as ethical, relational, and politically committed alternatives to hegemonic forms of masculinity, characterized by dominance, control, and emotional suppression. Framed as both identity practices and collective political endeavors, feminist masculinities promote care, vulnerability, and accountability, and seek to dismantle patriarchal formations through relational and intersectional praxis. In an empirical analysis, the article explores four projects—MenCare, MenEngage, Bróders, and KINDER—that apply caring masculinities in both international and grassroots contexts. Through their pedagogical, advocacy, and community-based strategies, these initiatives demonstrate the potential of feminist masculinities to transform cultural norms, shape policy-making, and foster connections between movements for gender, racial, and social justice. The findings demonstrate that feminist masculinities are most effective when grounded in broader feminist and intersectional agendas that integrate structural reforms with cultural change. The article concludes by contending that feminist masculinities present a robust counter-narrative to antifeminism and constitute a pragmatic basis for reimaging masculinity in directions that sustain equity, empathy, and democratic care. Policy interventions proposed include infusing gender-transformative curricula in education, institutionalizing support for care work, funding youth-led initiatives, and establishing feminist accountability mechanisms. In doing so, feminist masculinities are positioned not simply as reactive identities, but as proactive, systemic interventions essential to promoting more just and sustainable futures.